Legal Aspects of Election Participation For Persons With Limited Dual Citizenship Status - Nazheev Ilmi Haqqi; Mohammad Syaiful Aris (Universitas Negeri Surabaya, 2025)
Limited dual citizenship is a status given to someone who has 2 citizenships for a limited time. Limited dual citizenship is regulated in article 6 of Law Number 12 of 2006. Limited dual citizenship status is now owned by many people in Indonesia, one of which is due to intermarriage. The final limit for a person to determine their citizenship is 21 years of age. Remembering that citizenship status is something that cannot be separated from the name of rights and obligations. So regarding limited dual citizenship it involves many things regarding rules and prohibitions, but regarding what rights are obtained when someone still holds limited dual citizenship status. There are many kinds of rights that should be obtained by people who are citizens, especially Indonesian citizens, such as economic rights, educational rights and political rights. However, someone who has limited dual citizenship status does not necessarily get these rights, especially political rights which are closely related to constitutional affairs. Dual citizenship is limited as a temporary citizenship status. It is necessary to know what the limitations are while still holding that status using theoretical and comparative methods.